FLOOD CONTROL OF LAMONG RIVER, GRESIK DISTRICT - Oktaviani Dinda R; Iwan Wahjudijanto; Minarni Nur Trilita (Journal of Civil Engineering Science and Technology (CI-TECH), 2020)
Lamong River is located in East Java Province. The discharge of the Lamong River tends to be large, but it cannot be drained properly, so that the river overflows and causes Gresik Regency to experience flooding almost every year. The existing condition of the Lamong River is not able to accommodate the flood discharge. Therefore, it is planned to build a polder in the flood-prone areas of the Lamong River to accommodate the discharge that occurs. Polder on the Lamong River is planned with an entry discharge into the retention pool of 85% using a pump with a suction capacity of 5 m3 / s and 3 m3 / s. The dimensions of the Polder pond used in pond I are 530 m long, 530 m wide, 8 m deep, II pool size 540 m long, 540 m wide, 8 m deep, pool size III is 550 m long, 550 m wide, depth 8.5 m, the size of pool IV is 580 m long, 580 m wide, 9 m deep, for V pool size is 600 m long, 600 m wide, 9 m deep, and for pool VI size is 600 m long, 600 m wide m, 9 m depth. Each pool has 3 sluice gates with a size of 2 m per door with a door opening height of 1.32 m and a drain dimension of 3 m long, a channel width of 8 m, and a channel height of 3.46 m.